Separate O-grouping schemes for serotyping clinical isolates of Proteus vulgaris and Proteus mirabilis. - Penner, J L (1980)
Antisera were prepared against type strains of the original scheme of B. Perch (Acta Pathol. Microbiol. Scand. 25:703-714, 1948) and against newly defined types to produce separate schemes for O-grouping Proteus vulgaris and Proteus mirabilis. In assessing the schemes for their effectiveness it was found that 82% of 208 P. vulgaris isolates and 88% of 194 P. mirabilis isolates from two hospitals were typable. Only 3.4% of the P. vulgaris isolates agglutinated in P. mirabilis antisera, and 1.5% of the P. mirabilis agglutinated in P. vulgaris antisera, indicating that separation of the schemes would be more advantageous in routine typing. P. mirabilis of groups O3, O6, O10, O29, and O30 were most frequently isolated. Of the P. vulgaris isolates, 25% belonged to newly defined O-groups, and one of these was the largest with 14% of all isolates of this species. The application of serotyping using separate schemes for each species was advocated in epidemiological studies.